Manajemen Kelas di SMA Negeri 2 Model Kota Lubuklinggau - Marianita Marianita; M. Rusni Eka Putra; Ahmad Gawdy Prananosa (Journal Of Administration and Educational Management (ALIGNMENT), 2019)
The purpose of this study was to determine classroom management in the SMA Negeri 2 Model Lubuklinggau City. This study uses a qualitative approach with qualitative descriptive methods. Data collection techniques include; observation, interview and documentation. To determine the validity (trustworthiness) of the data required inspection techniques. There are four criteria that can be used to test the validity of data, namely the degree of trust (credibility), transferability, dependability and the certainty of data and research results, data analysis techniques using techniques; editing, category, displaying data and interpretation. Conclusion, classroom management in Lubuklinggau City Model 2 Senior High School is quite good, this can be seen from the classroom atmosphere and students' motivation in learning quite well and then also adequate facility support in managing classroom management. Then the communication between colleagues and school leaders runs well in classroom management, so the learning and teaching process in the classroom is quite conducive Keywords; Classroom Management, Model Schools